Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: Relevant categories of their functioning from the research perspective, a scoping review - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann (BMJ Open, 2021)
Objectives The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting Home, primary care. Participants Community-dwelling adults aged 75 years and above. Results From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the â € activities and participation' component. The most frequently identified categories were â € memory functions', â € dressing' and â € changing basic body position'. Conclusions This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-05
Keywords: general medicine (see internal medicine); geriatric medicine; primary care